The use of silver coating in hip megaprostheses: a systematic review. Issue 1 (January 2019) - Wyatt, Michael C; Foxall-Smith, Michael; Roberton, Andrew; Beswick, Andrew; Kieser, David C; Whitehouse, Michael R
Retrospective studies of silver-coated hip implants have demonstrated promising results and safety profile, however, the potential benefits are so far unproven in prospective studies. Silver-coated implants may have a role in patients undergoing revision or primary surgery with a high risk of infection but as yet there are no human studies investigating silver in primary hip arthroplasty. Adequately powered robust prospective studies are needed in this area to determine if silver-coated implants would be efficacious and cost-effective. The purpose of this systematic review article is to review the current literature regarding the use of silver in hip arthroplasty. Our review showed that there is some encouraging evidence that silver coatings can reduce infection.